Nuclear-grade cable for spent fuel aftertreatment and preparation method thereof
By using a combination of composite flame retardant and radiation-resistant agent in the nuclear-grade cable for spent fuel post-treatment, the problem of both flame retardant, radiation-resistant and mechanical properties of cable materials is solved, and high-performance cables are realized Material preparation for nuclear-grade cable outer sheath layer.
Patent Information
- Application Number
- CN202411239927.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing nuclear-grade cables for spent fuel post-treatment have both problems in flame retardancy, radiation resistance and mechanical properties. A single insulating layer cannot meet these needs at the same time, and the compatibility of inorganic flame retardants and organic materials is poor. Causes performance degradation.
Compound flame retardant is used to polymerize materials such as hydroxycyclotriphosphazene, tetrakis(4-hydroxybenzene)ethylene, oleic acid chloride and guar hydroxypropyl trimethylammonium chloride in a certain proportion, and combine inorganic flame retardant and radiation-resistant agents improve the flame retardant and radiation-resistant properties of cable materials through cross-linking treatment, and further improve compatibility through electron beam irradiation cross-linking.
Prepare cable materials with high flame retardant properties, high mechanical properties and high radiation resistance for use in the outer sheath layer of nuclear-grade cables, solving the problems of cable materials in both flame retardant, radiation resistance and mechanical properties. , reduce the amount of inorganic material added, improve dispersion and compatibility.
Smart Images

Figure BDA0005028929470000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and specifically discloses a nuclear-grade cable for spent fuel post-processing and a preparation method thereof. Background Art
[0002] Nuclear-grade cables for spent fuel reprocessing must have a high safety level and require excellent mechanical properties, flame retardancy, radiation resistance, stability, etc. A single insulation layer cannot have insulation, flame retardancy, radiation resistance, and durability at the same time, so nuclear-grade cables need to be wrapped in an outer sheath with high flame retardancy, high mechanical properties, and high radiation resistance;
[0003] Metal hydroxide flame retardants are abundant in source, cheap, and have good flame retardant effects. They are commonly used flame retardants in cable materials. However, due to the large difference in polarity between inorganic flame retardants and organic materials, they are not compatible. If a large amount is added, the mechanical properties and radiation resistance of the cable material will decrease, while a small amount cannot achieve a good flame retardant effect. In summary, it is of great significance to study a cable material that can be used for the outer sheath of nuclear-grade cables and has high flame retardant properties, high mechanical properties, and high radiation resistance. Summary of the invention
[0004] The object of the present invention is to provide a nuclear-grade cable for spent fuel reprocessing and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical scheme: A method for preparing a nuclear-grade cable for spent fuel reprocessing, comprising the following steps: S1: taking hydroxycyclotriphosphazene, tetra(4-hydroxyphenyl)ethylene, oleic acid chloride, guar gum hydroxypropyltrimethylammonium chloride, triethylamine, and a mixed solvent (chloroform, ether, and water in a volume ratio of 10:5:1), cooling to 3-5°C, dripping triethylamine under a nitrogen atmosphere, dripping phenoxyphosphoryl dichloride solution over 0.5-1h, stirring and reacting at 25-30°C for 10-12h, filtering, and rotary evaporation to obtain a composite flame retardant;
[0006] S2: adding polyethylene, inorganic flame retardant (aluminum hydroxide), composite flame retardant and anti-radiation agent into an internal mixer and mixing for 10 to 15 minutes, adding cross-linking agent trimethylol triacrylate, mixing evenly, extruding at 140 to 145° C., granulating to obtain a cable material; the cable material is used to prepare an outer sheath layer of a nuclear-grade cable;
[0007] S3: A conductor is formed by twisting multiple copper metal monofilaments, an insulating layer is wrapped outside the conductor, and a polyimide film is wrapped outside the insulating layer to form a wire core; multiple wire cores are twisted to form a cable core; the cable core is wrapped with a non-woven fabric wrapping tape layer and an outer sheath layer; the nuclear grade cable is obtained.
[0008] More optimally, the cable material includes the following raw materials: 50 to 60 parts of polyethylene, 10 to 15 parts of aluminum hydroxide, 8 to 10 parts of composite flame retardant, 2 to 4 parts of anti-radiation agent, and 1 to 1.5 parts of cross-linking agent; the polyethylene includes linear low-density polyethylene and maleic anhydride grafted linear low-density polyethylene in a mass ratio of (8 to 10):1.
[0009] More optimally, the composite flame retardant includes the following raw materials, calculated by mass: 15 to 20 parts of hydroxycyclotriphosphazene, 5 to 8 parts of tetra(4-hydroxyphenyl)ethylene, 1 to 2 parts of oleic acid chloride, 0.5 to 1 part of guar hydroxypropyltrimethylammonium chloride, 0.01 to 0.02 parts of triethylamine, 20 to 30 parts of mixed solvent, and 8 to 10 parts of triethylamine; the phenoxyphosphoryl dichloride solution includes the following raw materials, calculated by mass: 15 to 18 parts of phenoxyphosphoryl dichloride and 30 to 40 parts of mixed solvent.
[0010] More optimally, after the nuclear-grade cable is wrapped with an outer sheath layer, it is subjected to irradiation cross-linking treatment under an electron beam, and the irradiation dose is 100 to 120 KGy.
[0011] More optimally, the preparation of the hydroxy-containing cyclotriphosphazene comprises the following steps: Step 1: Take tetrahydrofuran and sodium hydride, mix them evenly, add a tetrahydrofuran solution of methoxyethanol dropwise at 20-30° C. under stirring, react at 30-35° C. for 30-35 min, cool to 4-5° C., add a tetrahydrofuran solution of hexachlorocyclotriphosphazene dropwise, react at 50-55° C. for 30-33 h, filter the reaction solution, evaporate tetrahydrofuran under reduced pressure, add dichloromethane, wash with distilled water until the aqueous phase is neutral, separate the organic phase, and evaporate dichloromethane under reduced pressure to obtain an intermediate;
[0012] Step 2: Take chloroform, intermediate and copper powder, add chloroform solution of trimethylsilyl iodide dropwise under stirring at 0-5°C, react at 25-28°C for 30-33h, filter the reaction solution after the reaction is completed, remove chloroform under reduced pressure, add sodium hydroxide methanol solution, stir at 20-25°C for 6-7h, filter the reaction solution, remove methanol under reduced pressure to obtain hydroxyl-containing cyclotriphosphazene.
[0013] More optimally, the tetrahydrofuran solution of methoxyethanol comprises the following raw materials, by weight: 150-160 parts of methoxyethanol and 50-60 parts of tetrahydrofuran; the tetrahydrofuran solution of hexachlorocyclotriphosphazene comprises the following raw materials, by weight: 100-120 parts of hexachlorocyclotriphosphazene and 100-120 parts of tetrahydrofuran; the intermediate comprises the following raw materials: 140-150 parts of sodium hydride and 150-200 parts of dichloromethane;
[0014] The chloroform solution of trimethyl iodosilane includes the following raw materials, calculated by mass: 60 to 65 parts of trimethyl iodosilane and 100 to 120 parts of chloroform; the hydroxy-containing cyclotriphosphazene includes the following raw materials, calculated by mass: 100 to 120 parts of intermediates, 0.8 to 1.5 parts of copper powder, and 600 to 800 parts of sodium hydroxide methanol solution; the concentration of the sodium hydroxide methanol solution is 0.5 to 0.6 mol / L.
[0015] More optimally, the preparation of the anti-radiation agent includes the following steps: taking lamellar boron nitride and adding it into water to disperse it evenly, adding tungsten chloride, adding ammonia water (25wt%) dropwise while stirring to make the pH value be 9-10, carrying out a hydrothermal reaction at 180-185°C in a hydrothermal reactor for 10-12h, centrifugally separating, washing, and drying to obtain the anti-radiation agent.
[0016] More optimally, the anti-radiation agent includes the following raw materials, calculated by weight: 250-300 parts of water, 2-3 parts of lamellar boron nitride, and 3-5 parts of tungsten chloride.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a cable material for a nuclear-grade cable outer sheath is prepared, which contains a composite flame retardant; the composite flame retardant is obtained by polymerizing hydroxycyclotriphosphazene, tetra(4-hydroxyphenyl)ethylene, oleic acid chloride, guar gum hydroxypropyltrimethylammonium chloride, and phenoxyphosphoryl dichloride in a certain proportion; the phosphazene compound has a unique P, N hybrid structure, has good flame retardant performance, and the alternating N=P conjugated π bond structure has a scattering effect on electron beams and has radiation resistance; tetra(4-hydroxyphenyl)ethylene provides multiple benzene rings, improves the radiation resistance and increases the mechanical properties of the cable material, but the added amount should not be too much, because too much benzene ring will lead to brittleness of the cable material. Increase, but it is not good for mechanical properties; oleic acid chloride provides a long chain structure to improve the flexibility of cable materials, and on the other hand, it acts as a lubricant to improve the processing performance of cable materials; guar gum hydroxypropyltrimethylammonium chloride is hydrophilic, and can act as a dispersant after being introduced into the composite flame retardant, which is helpful for the dispersion of inorganic flame retardants and anti-radiation agents in subsequent steps; phenoxyphosphoryl dichloride is a cross-linking agent, and it contains P and benzene rings, which also helps to improve the performance of the composite flame retardant; the composite flame retardant prepared by this method has a large molecular weight and contains a double bond structure, which improves the compatibility with polyethylene, the main material of the cable material, can reduce the problem of auxiliary agent migration, and reduce the performance degradation caused by poor dispersibility;
[0018] The composite flame retardant and the inorganic flame retardant are added to the cable material in a certain proportion, which can reduce the amount of inorganic material added in the cable material and reduce the problems of poor dispersibility and performance degradation caused by excessive addition of inorganic material; since the composite flame retardant has the functions of lubrication and dispersing, there is no need to add additional lubricants or dispersants, which effectively inhibits the migration of small molecule additives and also improves the dispersibility of inorganic flame retardants and radiation inhibitors; the cable material contains a cross-linking agent, and after the outer sheath layer is made, it is necessary to perform irradiation cross-linking treatment under an electron beam to further improve the degree of cross-linking and also improve the compatibility of the composite flame retardant and polyethylene; finally, a cable material with high flame retardancy, high mechanical properties and high radiation resistance is obtained, which can be used for the preparation of the outer sheath layer of nuclear-grade cables. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The following parts are by mass unless otherwise specified;
[0021] Example 1: S1: Under room temperature conditions, 300 parts of water are added to a reaction vessel equipped with a stirrer, a reflux condenser and a flow of dry nitrogen, 3 parts of lamellar boron nitride are added, and the mixture is evenly dispersed. 4 parts of tungsten chloride are added, and ammonia water is added dropwise while stirring to adjust the pH to 10. The mixture is subjected to a hydrothermal reaction at 185° C. for 12 hours in a hydrothermal reactor, and the mixture is centrifuged, washed and dried to obtain an anti-radiation agent.
[0022] S2: Take 350 parts of tetrahydrofuran and 150 parts of sodium hydride, mix them evenly, add a tetrahydrofuran solution of methoxyethanol (150 parts of methoxyethanol, 60 parts of tetrahydrofuran) dropwise at 25°C with stirring, react at 35°C for 30 minutes, cool to 5°C, add a tetrahydrofuran solution of hexachlorocyclotriphosphazene (100 parts of hexachlorocyclotriphosphazene, 120 parts of tetrahydrofuran), react at 55°C for 30 hours, filter the reaction solution, remove tetrahydrofuran under reduced pressure, add 200 parts of dichloromethane, wash with distilled water until the aqueous phase is neutral, separate the organic phase, and remove dichloromethane under reduced pressure to obtain an intermediate;
[0023] S3: Take 450 parts of chloroform, 120 parts of the intermediate, and 1 part of copper powder, add a chloroform solution of trimethylsilane iodide (60 parts of trimethylsilane iodide, 120 parts of chloroform) dropwise under stirring at 5°C, react at 25°C for 33 hours, filter the reaction solution after the reaction is completed, evaporate the chloroform under reduced pressure, add 800 parts of 0.6 mol / L sodium hydroxide methanol solution, stir and react at 25°C for 6 hours, filter the reaction solution, and evaporate the methanol under reduced pressure to obtain hydroxy-containing cyclotriphosphazene;
[0024] S4: Take 18 parts of hydroxycyclotriphosphazene, 6 parts of tetra(4-hydroxyphenyl)ethylene, 1.5 parts of oleic acid chloride, 0.8 parts of guar hydroxypropyltrimethylammonium chloride, 0.01 parts of triethylamine, and 25 parts of a mixed solvent, cool to 5°C, add 10 parts of triethylamine dropwise under a nitrogen atmosphere, add a phenoxyphosphoryl dichloride solution (15 parts of phenoxyphosphoryl dichloride, 35 parts of a mixed solvent) dropwise over 0.5h, react with stirring at 28°C for 12h, filter, and rotary evaporate to obtain a composite flame retardant;
[0025] S5: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 12 parts of aluminum hydroxide, 9 parts of composite flame retardant, and 3 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1 part of cross-linking agent trimethylol triacrylate is added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0026] Example 2: S1: Under room temperature conditions, 300 parts of water are added to a reaction vessel equipped with a stirrer, a reflux condenser and a flow of dry nitrogen, 3 parts of lamellar boron nitride are added, and the mixture is evenly dispersed. 5 parts of tungsten chloride are added, and ammonia water is added dropwise while stirring to adjust the pH to 10. The mixture is subjected to a hydrothermal reaction at 185° C. for 12 hours in a hydrothermal reactor, and the mixture is centrifuged, washed and dried to obtain an anti-radiation agent.
[0027] S2: Take 350 parts of tetrahydrofuran and 150 parts of sodium hydride, mix them evenly, add a tetrahydrofuran solution of methoxyethanol (150 parts of methoxyethanol, 60 parts of tetrahydrofuran) dropwise at 25°C with stirring, react at 35°C for 30 minutes, cool to 5°C, add a tetrahydrofuran solution of hexachlorocyclotriphosphazene (100 parts of hexachlorocyclotriphosphazene, 120 parts of tetrahydrofuran), react at 55°C for 30 hours, filter the reaction solution, remove tetrahydrofuran under reduced pressure, add 200 parts of dichloromethane, wash with distilled water until the aqueous phase is neutral, separate the organic phase, and remove dichloromethane under reduced pressure to obtain an intermediate;
[0028] S3: Take 450 parts of chloroform, 120 parts of the intermediate, and 1.5 parts of copper powder, add a chloroform solution of trimethylsilane iodide (60 parts of trimethylsilane iodide, 120 parts of chloroform) dropwise under stirring at 5°C, react at 25°C for 33 hours, filter the reaction solution after the reaction is completed, evaporate the chloroform under reduced pressure, add 800 parts of 0.6 mol / L sodium hydroxide methanol solution, stir and react at 25°C for 6 hours, filter the reaction solution, and evaporate the methanol under reduced pressure to obtain hydroxy-containing cyclotriphosphazene;
[0029] S4: Take 20 parts of hydroxy-containing cyclotriphosphazene, 8 parts of tetra(4-hydroxyphenyl)ethylene, 2 parts of oleic acid chloride, 1 part of guar hydroxypropyltrimethylammonium chloride, 0.01 parts of triethylamine, and 25 parts of a mixed solvent, cool to 5°C, add 10 parts of triethylamine dropwise under a nitrogen atmosphere, add a phenoxyphosphoryl dichloride solution (15 parts of phenoxyphosphoryl dichloride, 35 parts of a mixed solvent) dropwise over 0.5h, react with stirring at 28°C for 12h, filter, and rotary evaporate to obtain a composite flame retardant;
[0030] S5: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 10 parts of aluminum hydroxide, 10 parts of composite flame retardant and 4 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1.5 parts of cross-linking agent trimethylol triacrylate are added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0031] Example 3: S1: Under room temperature conditions, 300 parts of water are added to a reaction vessel equipped with a stirrer, a reflux condenser and a dry nitrogen gas, 3 parts of lamellar boron nitride are added, and the mixture is evenly dispersed. 3 parts of tungsten chloride are added, and ammonia water is added dropwise while stirring to adjust the pH to 10. The mixture is subjected to a hydrothermal reaction at 185° C. for 12 hours in a hydrothermal reactor, and the mixture is centrifuged, washed and dried to obtain an anti-radiation agent.
[0032] S2: Take 350 parts of tetrahydrofuran and 140 parts of sodium hydride, mix them evenly, add a tetrahydrofuran solution of methoxyethanol (150 parts of methoxyethanol, 60 parts of tetrahydrofuran) dropwise at 25°C with stirring, react at 35°C for 30 minutes, cool to 5°C, add a tetrahydrofuran solution of hexachlorocyclotriphosphazene (100 parts of hexachlorocyclotriphosphazene, 120 parts of tetrahydrofuran), react at 55°C for 30 hours, filter the reaction solution, remove tetrahydrofuran under reduced pressure, add 200 parts of dichloromethane, wash with distilled water until the aqueous phase is neutral, separate the organic phase, and remove dichloromethane under reduced pressure to obtain an intermediate;
[0033] S3: Take 450 parts of chloroform, 100 parts of the intermediate, and 0.8 parts of copper powder, add a chloroform solution of trimethylsilane iodide (60 parts of trimethylsilane iodide, 120 parts of chloroform) dropwise under stirring at 0°C, react at 25°C for 33 hours, filter the reaction solution after the reaction is completed, evaporate the chloroform under reduced pressure, add 800 parts of 0.6 mol / L sodium hydroxide methanol solution, stir and react at 25°C for 6 hours, filter the reaction solution, and evaporate the methanol under reduced pressure to obtain hydroxy-containing cyclotriphosphazene;
[0034] S4: Take 15 parts of hydroxycyclotriphosphazene, 5 parts of tetra(4-hydroxyphenyl)ethylene, 1 part of oleic acid chloride, 0.5 parts of guar hydroxypropyltrimethylammonium chloride, 0.01 parts of triethylamine, and 25 parts of a mixed solvent, cool to 5°C, add 8 parts of triethylamine dropwise under a nitrogen atmosphere, add a phenoxyphosphoryl dichloride solution (15 parts of phenoxyphosphoryl dichloride, 35 parts of a mixed solvent) dropwise over 0.5h, react with stirring at 28°C for 12h, filter, and rotary evaporate to obtain a composite flame retardant;
[0035] S5: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 15 parts of aluminum hydroxide, 8 parts of composite flame retardant, and 2 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1 part of cross-linking agent trimethylol triacrylate is added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0036] Comparative Example 1 (the raw materials in the composite flame retardant are changed, and the remaining steps are consistent with those in Example 1): S1: preparing an anti-radiation agent, the method is the same as that in Example 1;
[0037] S2: preparing hydroxyl-containing cyclotriphosphazene in the same manner as in Example 1;
[0038] S3: Take 15 parts of hydroxy-containing cyclotriphosphazene, 12 parts of tetra(4-hydroxyphenyl)ethylene, 0.01 parts of triethylamine, and 25 parts of a mixed solvent, cool to 5°C, add 10 parts of triethylamine dropwise under a nitrogen atmosphere, add a phenoxyphosphoryl dichloride solution (15 parts of phenoxyphosphoryl dichloride, 35 parts of a mixed solvent) dropwise over 0.5h, react with stirring at 28°C for 12h, filter, and rotary evaporate to obtain a composite flame retardant;
[0039] S4: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 12 parts of aluminum hydroxide, 9 parts of composite flame retardant and 3 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1 part of cross-linking agent trimethylol triacrylate is added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0040] Comparative Example 2 (changing the amount of raw materials added in the cable material, and the other method steps are consistent with Example 1): S1: preparing an anti-radiation agent, the method is the same as Example 1;
[0041] S2: preparing hydroxyl-containing cyclotriphosphazene in the same manner as in Example 1;
[0042] S3: Take 18 parts of hydroxycyclotriphosphazene, 6 parts of tetra(4-hydroxyphenyl)ethylene, 1.5 parts of oleic acid chloride, 0.8 parts of guar hydroxypropyltrimethylammonium chloride, 0.01 parts of triethylamine, and 25 parts of a mixed solvent, cool to 5°C, add 10 parts of triethylamine dropwise under a nitrogen atmosphere, add a phenoxyphosphoryl dichloride solution (15 parts of phenoxyphosphoryl dichloride, 35 parts of a mixed solvent) dropwise over 0.5h, stir and react at 28°C for 12h, filter, and rotary evaporate to obtain a composite flame retardant;
[0043] S4: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 20 parts of aluminum hydroxide, 5 parts of composite flame retardant and 3 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1 part of cross-linking agent trimethylol triacrylate is added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0044] Comparative Example 3: (the amount of raw materials added in the cable material is changed, and the other method steps are consistent with Example 1): S1: preparing an anti-radiation agent, the method is the same as Example 1;
[0045] S2: preparing hydroxyl-containing cyclotriphosphazene in the same manner as in Example 1;
[0046] S3: Take 18 parts of hydroxycyclotriphosphazene, 6 parts of tetra(4-hydroxyphenyl)ethylene, 1.5 parts of oleic acid chloride, 0.8 parts of guar hydroxypropyltrimethylammonium chloride, 0.01 parts of triethylamine, and 25 parts of a mixed solvent, cool to 5°C, add 10 parts of triethylamine dropwise under a nitrogen atmosphere, add a phenoxyphosphoryl dichloride solution (15 parts of phenoxyphosphoryl dichloride, 35 parts of a mixed solvent) dropwise over 0.5h, stir and react at 28°C for 12h, filter, and rotary evaporate to obtain a composite flame retardant;
[0047] S4: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 8 parts of aluminum hydroxide, 15 parts of composite flame retardant and 3 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1 part of cross-linking agent trimethylol triacrylate is added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0048] Comparative Example 4 (the preparation method of the composite flame retardant is changed, and the remaining steps are consistent with those of Example 1): S1: preparing an anti-radiation agent, the method is the same as that of Example 1;
[0049] S2: preparing hydroxyl-containing cyclotriphosphazene in the same manner as in Example 1;
[0050] S3: Take 18 parts of hydroxycyclotriphosphazene, 6 parts of tetra(4-hydroxyphenyl)ethylene, 1.5 parts of oleic acid chloride, 0.8 parts of guar hydroxypropyltrimethylammonium chloride, and 15 parts of phenoxyphosphoryl dichloride, mix them, and obtain a composite flame retardant;
[0051] S4: 50 parts of linear low-density polyethylene, 6 parts of maleic anhydride grafted linear low-density polyethylene, 12 parts of aluminum hydroxide, 9 parts of composite flame retardant and 3 parts of anti-radiation agent are mixed in an internal mixer at 150°C for 15 minutes, and then 1 part of cross-linking agent trimethylol triacrylate is added, mixed evenly, extruded at 140°C, and granulated to obtain cable material; the cable material is used to prepare the outer sheath layer of nuclear-grade cable, and after wrapping the outer sheath layer, it is irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 110KGy.
[0052] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: lamellar boron nitride (NS-BN, Changzhou Lima); tungsten chloride (CAS: 13283-01-7); ether (CAS: 60-29-7); tetrahydrofuran (CAS: 109-99-9); sodium hydride (CAS: 7646-69-7); methoxyethanol (CAS: 109-86-4); hexachlorocyclotriphosphazene (CAS: 940-71-6); dichloromethane (CAS: 75-09-2); chloroform (CAS: 67-66-3); copper powder (ML-Cu-W01, Zhejiang Manli Nanotechnology Co., Ltd. Technology Co., Ltd.); trimethyl iodosilane (CAS: 16029-98-4); sodium hydroxide (CAS: 1310-73-2); tetra(4-hydroxyphenyl)ethylene (CAS: 119301-59-6); guar hydroxypropyltrimethylammonium chloride (S26747, Shanghai Yuanye); trimethylol triacrylate (Y57622, Shanghai Yuanye); oleic acid chloride (CAS: 112-77-6); triethylamine (CAS: 121-44-8); phenoxyphosphoryl dichloride (CAS: 770-12-7); linear low-density polyethylene (218WJ, SABIC); maleic anhydride grafted linear low-density polyethylene (Bai Ling OE); aluminum hydroxide (S30353, Shanghai Yuanye).
[0053] Experiment: The cable materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to irradiation crosslinking treatment at a power and energy of 10 KW and 10 MeV electron beam, respectively, and an irradiation dose of 110 KGy to obtain samples; (1) with reference to GB / T2406.2-2009 standard, the oxygen index was tested; (2) with reference to GB / T2951.11-2008, the tensile strength was tested; (3) with reference to IEC 61244:2014 and GB / T2951.11-2008, the tensile strength after irradiation of 1500 kGy was tested; the specific data are shown in the table below;
[0054]
[0055] Conclusion: Comparative Example 1 changes the raw materials in the composite flame retardant, the amount of tetra(4-hydroxyphenyl)ethylene added is increased, oleic acid chloride and guar hydroxypropyltrimethylammonium chloride are not added, and the performance is not as good as the embodiment, which shows that the composite flame retardant formula is of great significance; Comparative Examples 2 and 3 change the amount of raw materials added in the cable material, and the performance decreases; it can be seen that the ratio of inorganic flame retardant to composite flame retardant in the cable material needs to be controlled; Comparative Example 4 changes the preparation method of the composite flame retardant, and does not compound hydroxycyclotriphosphazene, tetra(4-hydroxyphenyl)ethylene, oleic acid chloride, guar hydroxypropyltrimethylammonium chloride, and phenoxyphosphoryl dichloride, but directly adds them, and the tensile strength decreases a lot after irradiation, which may be due to the compatibility and migration of small molecule additives. Problems; In summary, the cable material prepared by the present invention has good flame retardancy, good mechanical properties, and good radiation resistance, and can be used for the preparation of nuclear-grade cable outer sheaths.
[0056] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a nuclear-grade cable for spent fuel reprocessing, characterized in that: The following steps are involved: S1: Take hydroxycyclotriphosphazene, tetra(4-hydroxyphenyl)ethylene, oleic acid chloride, guar gum hydroxypropyltrimethylammonium chloride, triethylamine, and a mixed solvent, cool to 3-5°C, add triethylamine dropwise under a nitrogen atmosphere, add phenoxyphosphoryl dichloride solution dropwise over 0.5-1h, react with stirring at 25-30°C for 10-12h, filter, and rotary evaporate to obtain a composite flame retardant; S2: adding polyethylene, inorganic flame retardant, composite flame retardant and anti-radiation agent into an internal mixer and mixing for 10 to 15 minutes, adding a cross-linking agent, mixing evenly, extruding at 140 to 145° C., and granulating to obtain a cable material; the cable material is used to prepare an outer sheath layer of a nuclear-grade cable; S3: A conductor is formed by twisting multiple copper metal monofilaments, an insulating layer is wrapped outside the conductor, and a polyimide film is wrapped outside the insulating layer to form a wire core; multiple wire cores are twisted to form a cable core; the cable core is wrapped with a non-woven fabric wrapping tape layer and an outer sheath layer; the nuclear grade cable is obtained.
2. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 1, characterized in that: The cable material comprises the following raw materials: 50 to 60 parts of polyethylene, 10 to 15 parts of inorganic flame retardant, 8 to 10 parts of composite flame retardant, 2 to 4 parts of anti-radiation agent, and 1 to 1.5 parts of cross-linking agent; the polyethylene comprises linear low-density polyethylene and maleic anhydride grafted linear low-density polyethylene in a mass ratio of (8 to 10):
1.
3. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 1, characterized in that: The composite flame retardant comprises the following raw materials, calculated by weight: 15 to 20 parts of hydroxy-containing cyclotriphosphazene, 5 to 8 parts of tetra(4-hydroxyphenyl)ethylene, 1 to 2 parts of oleic acid chloride, 0.5 to 1 part of guar hydroxypropyltrimethylammonium chloride, 0.01 to 0.02 parts of triethylamine, 20 to 30 parts of mixed solvent, and 8 to 10 parts of triethylamine; the phenoxyphosphoryl dichloride solution comprises the following raw materials, calculated by weight: 15 to 18 parts of phenoxyphosphoryl dichloride and 30 to 40 parts of mixed solvent.
4. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 1, characterized in that: After the nuclear-grade cable is wrapped with an outer sheath layer, it is subjected to irradiation cross-linking treatment under an electron beam, and the irradiation dose is 100 to 120 KGy.
5. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 1, characterized in that: Preparation of the Hydroxycyclotriphosphazene The method comprises the following steps: step 1: taking tetrahydrofuran and sodium hydride, mixing them evenly, dropping a tetrahydrofuran solution of methoxyethanol under stirring at 20-30° C., reacting at 30-35° C. for 30-35 minutes, cooling to 4-5° C., dropping a tetrahydrofuran solution of hexachlorocyclotriphosphazene, reacting at 50-55° C. for 30-33 hours, filtering the reaction liquid, distilling off tetrahydrofuran under reduced pressure, adding dichloromethane, washing with distilled water until the aqueous phase is neutral, separating the organic phase, and distilling off dichloromethane under reduced pressure to obtain an intermediate; Step 2: Take chloroform, intermediate and copper powder, add chloroform solution of trimethylsilyl iodide dropwise under stirring at 0-5°C, react at 25-28°C for 30-33h, filter the reaction solution after the reaction is completed, remove chloroform under reduced pressure, add sodium hydroxide methanol solution, stir at 20-25°C for 6-7h, filter the reaction solution, remove methanol under reduced pressure to obtain hydroxyl-containing cyclotriphosphazene.
6. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 5, characterized in that: The tetrahydrofuran solution of methoxyethanol comprises the following raw materials, calculated by weight: 150-160 parts of methoxyethanol and 50-60 parts of tetrahydrofuran; the tetrahydrofuran solution of hexachlorocyclotriphosphazene comprises the following raw materials, calculated by weight: 100-120 parts of hexachlorocyclotriphosphazene and 100-120 parts of tetrahydrofuran; the intermediate comprises the following raw materials: 140-150 parts of sodium hydride and 150-200 parts of dichloromethane; The chloroform solution of trimethyl iodosilane includes the following raw materials, calculated by weight: 60-65 parts of trimethyl iodosilane and 100-120 parts of chloroform; the hydroxy-containing cyclotriphosphazene includes the following raw materials, calculated by weight: 100-120 parts of intermediate, 0.8-1.5 parts of copper powder, and 600-800 parts of sodium hydroxide methanol solution; The concentration of the sodium hydroxide methanol solution is 0.5-0.6 mol / L.
7. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 1, characterized in that: The preparation of the anti-radiation agent comprises the following steps: adding boron nitride flakes into water and dispersing the flakes uniformly, adding tungsten chloride, adding ammonia water dropwise while stirring to adjust the pH value to 9-10, performing a hydrothermal reaction at 180-185° C. in a hydrothermal reactor for 10-12 hours, centrifugally separating, washing and drying to obtain the anti-radiation agent.
8. The method for preparing a nuclear-grade cable for spent fuel reprocessing according to claim 7, characterized in that: The anti-radiation agent comprises the following raw materials, calculated by weight: 250-300 parts of water, 2-3 parts of lamellar boron nitride, and 3-5 parts of tungsten chloride.
9. A nuclear-grade cable prepared according to the method for preparing a nuclear-grade cable for spent fuel reprocessing according to any one of claims 1 to 8.
Citation Information
Patent Citations
Synthetic method of 6(4-hydroxyl ethyoxyl) cyclotriphophazene
CN102766167A
Polyfatty acid salt compounds for treating fibrous amino acid-based substrates, in particular hair
CN117642376A
Cited By
Tensile composite cable for robot and preparation method thereof
CN120527071A
A tensile-resistant composite cable for a robot and a method of manufacturing the same
CN120527071B